2023
DOI: 10.3390/nu15030502
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Attenuates Hypertension via Inhibiting NF-κB-Mediated Inflammation and PI3K/Akt Signaling Pathway in the Hypothalamic Paraventricular Nucleus

Abstract: Background: Luteolin is widely distributed among a number of vegetal species worldwide. The pharmacological effects of luteolin are diverse and amongst antioxidant, free radical scavenging, and anti-inflammatory activities. Preliminary study showed that luteolin can ameliorate hypertension. However, the precise mechanism needs further investigation. There is no evidence that luteolin affects the paraventricular nucleus of the hypothalamus (PVN), a brain nucleus associated with a critical neural regulator of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The animal study protocol was approved by the Animal Care and Use Committee of Xi’an Jiaotong University (protocol code No. 2020–62 and date of approval 25 March 2020) ( Gao et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal study protocol was approved by the Animal Care and Use Committee of Xi’an Jiaotong University (protocol code No. 2020–62 and date of approval 25 March 2020) ( Gao et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 1 week of acclimatization, Dahl S rats were divided into four groups according to diet type: (1) NSD + PVN vehicle group ( n = 7): rats were fed with food containing 0.3% NaCl and PVN infusion with vehicle; (2) NSD + capsaicin group ( n = 7): rats were fed with food containing 0.3% NaCl and PVN infusion with capsaicin; (3) HSD + PVN vehicle group ( n = 7): rats were fed with food containing 8% NaCl and PVN infusion with vehicle; (4) HSD + capsaicin group ( n = 7): rats were fed with food containing 8% NaCl and PVN infusion with capsaicin. The determination of the effective dose of capsaicin is based on our pilot study combined with previous studies ( Qi et al, 2022 ; Gao et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Luteolin, a flavone abundant in fruits, vegetables, and flowers, possesses anti-inflammatory, antihypertensive [ 161 ], and anticancer properties, which are related to its ability to induce apoptosis, inhibit proliferation, and prevent angiogenesis [ 162 ]. Notably, it modulates the JNK protein in cancer cells [ 163 ], suppresses anti-apoptotic proteins like Bcl-2 and Bcl-xL, activates caspases, and triggers DNA damage through ROS, thereby activating p53 [ 164 ].…”
Section: Current Plant-based Natural Products Aptamers and Delivery S...mentioning
confidence: 99%
“…The ability of LAE extract to reduce VCAM-1 and ICAM-1 expression may be an essential mechanism for the extract's anti-inflammatory effects. Several studies have reported the activation of the PI3K/Akt pathway and its contribution to the upregulated production of inflammatory cytokines in activated endothelial cells [28,29]. Consequently, the effects of LAE extract on LPS-induced PI3K/Akt activation in HUVECs were analyzed.…”
Section: Lae Extract Attenuates Inflammatory Signaling Pathways In Hu...mentioning
confidence: 99%